House prices and land prices under the microscope: a property-level analysis for the Washington, DC area - Edward J. Pinto; Stephen D. Oliner; Morris A. Davis (American Enterprise Institute (AEI), 2014)
In this paper, we use a new property-level dataset to estimate the price of land since 2000 for nearly 600,000 detached single-family homes in the Washington, DC metro area. We employ these estimates to characterize the recent boom/bust cycle in land prices and house prices in the Washington area at a fine level of geography. The data show that land prices were more volatile than house prices everywhere, but especially so in the areas where land was inexpensive in 2000. In those areas, the land share of property value jumped during the boom, and this rise in the land share was a useful predictor of the subsequent crash in house prices. These results highlight the value of focusing on land for assessing house-price risk. In ongoing work, we are exploring how much of the spatial variation in land-price changes can be linked to high-risk mortgage lending and fundamentals such as housing rents, income growth, and employment.
Keywords: R; 330; Housing finance; US Housing Market; Housing Center: Research